2022
DOI: 10.1177/11795549221103200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor- And Progesterone Receptor-Positive Thresholds in Predicting the Recurrence of Early Low-Risk Endometrial Cancer

Abstract: Background: Estrogen receptors (ER) and progesterone receptors (PR) have important prognostic value in endometrial cancer, but there is no recognized positive immunohistochemical threshold for predicting the recurrence of early low-risk endometrial cancer. The purpose of this study was to clarify the optimal positive thresholds of the immunohistochemical parameters the ER and PR in early low-risk endometrial cancer. Methods: A total of 332 patients with stage IA endometrial cancer were enrolled from the First … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
2
5
2
Order By: Relevance
“…Previous studies have shown that ER and PR status and Ki67 and P53 indices are independent prognostic factors for EC recurrence. 1,7,8,10,[15][16][17][18][19] Although ER, PR, and P53 were found to be independent risk factors for recurrence in univariate analysis in our study, ER lost its significance in multivariate analysis. The reason why ER lost its significant may be that P53, PR are more strongly associated with early low-risk EC recurrence or due to the small number of patients.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Previous studies have shown that ER and PR status and Ki67 and P53 indices are independent prognostic factors for EC recurrence. 1,7,8,10,[15][16][17][18][19] Although ER, PR, and P53 were found to be independent risk factors for recurrence in univariate analysis in our study, ER lost its significance in multivariate analysis. The reason why ER lost its significant may be that P53, PR are more strongly associated with early low-risk EC recurrence or due to the small number of patients.…”
Section: Discussioncontrasting
confidence: 73%
“…In the study of Li et al, which is similar to our study in terms of patient population, it has been shown that the P53 index is a prognostic factor for recurrence in early low-risk EC; but the optimal cut-ff value of P53 index for predicting the recurrence of early low-risk EC has not been determined. 7 Although the study of Li et al is similar to our study in terms of patient population, it has not been clearly stated which patient group underwent pelvic or paraaortic lymph node dissection. Paraaortic lymph node dissection was not performed in any patient in our study and pelvic lymphadenectomy was performed for patients whose frozen section analysis reveals tumor size ≥2 cm and grade 2 histology or in case of clinical suspicion.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations